STRUKTUR POPULASI CACING TANAH DI HUTAN SEKUNDER DAN AGROFORESTRI KOPI DESA KUTAGUGUNG KECAMATAN NAMAN TERAN KABUPATEN KARO - Aini Qomariah Manurung (UNIVERSITAS LABUHANBATU, 2019)
Research on the structure population of earthworm in secondary forest and coffee agroforestry Kutagugung Village, District Naman Teran, Karo, North Sumatra was conducted in January 2013. The aim of research was to determinate type earthworm, populations and its relation to environmental conditions. The method used is purposive random sampling with square method, hand sorting and environmental conditions (temperature, pH, rH, C-organik, N, P dan K). Amynthas sp., Pheretima sp. and Pontoscolex corethrurus found at both locations, while Peryonix sp. only found in coffee agroforestry. The highest density found in coffee agroforestry (283.73 ind/m2) followed by secondary forest (78.93 ind/m2). Types of earthworm bioindicator in secondary forest is Pontoscolex corethrurus (KR= 60.81%, FK= 60%) and Pheretima sp. (KR= 36.49%, FK= 53%), whereas in the coffee agroforestry only found Pontoscolex corethrurus (KR= 91.73%, FK= 100%). Pearson correlation analysis results indicate the number of individual earthworms were significantly positively correlated to the secondary forest soil pH (P= 0.544, α= 0.05). Keywords: coffee agroforestry, district karo, earth worm, population, secondary forest